Psychological Challenges facing Primary School Children in Windhoek, Namibia: Perspectives of Teachers - Uupindi, Victoria N. (University of the Witwatersrand, Johannesburg, 2024)
The study aimed to explore the psychological challenges that primary school children were facing through the perspectives of teachers. The study also investigated the support system that was available to mitigate these challenges both at school and in the community. Urie Bronfenbrenner’s Bio-Ecological Theory of human development was used as a theoretical framework to comprehend and discuss the findings of the study. The study employed a Qualitative Research approach using a phenomenological perspective. The data was collected from three primary schools in Windhoek Namibia, from a total of eight participants using face-to-face recorded interviews. The participants were recruited using a snowball sampling technique that allowed the researcher to network for the next participant. The findings indicated that children are indeed influenced by their surroundings, experiencing many challenges such as those associated with Covid-19, those created by home circumstances, negative behavior, emotional distress and challenges associated with their schooling such as low school performance. The study revealed that various systems like the schools, churches and community members all collaborate to help primary school children navigate through their challenges.
A research report submitted in fulfillment of the requirements for the Masters in Psychology , In the Faculty of Humanities, School of School of Human and Community Development, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; PSYCHOLOGICAL CHALLENGES; PSYCHOLOGICAL INTERVENTION; SCHOOL-BASED SUPPORT; SOCIAL FACTORS; PSYCHOLOGICAL FACTORS; BIO ECOLOGICAL THEORY OF HUMAN DEVELOPMENT; SDG-3: Good health and well-being